Reduction of Low-Frequency Vessel Noise in Monterey Bay National Marine Sanctuary During the COVID-19 Pandemic - Ryan, John P.; Joseph, John E.; Margolina, Tetyana; Hatch, Leila T.; Azzara, Alyson; Reyes, Alexis; Southall, Brandon L.; DeVogelaere, Andrew; Peavey Reeves, Lindsey E.; Zhang, Yanwu; Cline, Danelle E.; Jones, Brent; et al. (Frontiers in Marine Science, 2021)
Low-frequency sound from large vessels is a major, global source of ocean noise that can interfere with acoustic communication in a variety of marine animals. Changes in vessel activity provide opportunities to quantify relationships between vessel traffic levels and soundscape conditions in biologically important habitats. Using continuous deep-sea (890 m) recordings acquired 20 km from offshore shipping lanes, we observed a quieting of low-frequency noise within Monterey Bay National Marine Sanctuary (California, USA) associated with changes in vessel traffic during the onset of the COVID-19 pandemic. The frequency band 31–100 Hz effectively captured large-vessel noise while minimizing potential biases from geological and biological sources. Monthly median spectrum levels (MSL) in this band decreased during January–June 2020, as much as 2.7 dB re 1 uPa2 Hz-1 below levels in the prior two years, and they began returning to those levels by July 2020. During 2020 MSL were strongly correlated with large-vessel total gross tonnage derived from economic data, summed across all California ports (r = 0.89, p < 0.01). They were also highly correlated with regional presence of large vessels, quantified from Automatic Identification System (AIS) line-of-sight vessel tracking data and weighted by vessel speed and inverse distance from the recorder (r = 0.94, p < 0.01). Within the three-year study period, February–June 2020 exhibited anomalously quiet low-frequency noise and anomalously low statewide port activity and regional large-vessel presence. While likely a short-term change, the maximum 2020 quieting represented nearly a halving of acoustic intensity in a frequency band used by baleen whales to communicate. This illustrates the influence of offshore large-vessel traffic on sound and protected species in marine sanctuary habitats.